Minimally Invasive Treatments for Lower Urinary Tract Symptoms: A Systematic Review - Christine; Sisca (International Medical Journal Corp. Ltd, 2024)
Introduction: Bladder outlet obstruction (BOO) significantly contributes to lower urinary tract symptoms (LUTS) in men. When medical treatments are insufficient, surgical options such as transurethral resection of the prostate (TURP) are considered standard. However, TURP has drawbacks, including the need for general or spinal anesthesia, hospitalization, and potential complications like retrograde ejaculation, hematuria, clot retention, and urethral stricture. In response, less invasive treatments have been developed, though their functional outcomes have often been less satisfactory than TURP, leading to their exclusion from recent guidelines. Methods: A thorough search was conducted using keywords related to MITs for LUTS, with inclusion criteria focusing on randomized controlled trials (RCTs) published in English. Studies were selected based on their relevance and adherence to the inclusion criteria, followed by a rigorous quality assessment and data synthesis. Results: From an initial pool of studies, five key papers were selected for detailed analysis. These studies included comparisons of prostatic artery embolization (PAE) with TURP, aquablation with sham procedures, and various other MITs. Conclusion: This review highlights the potential of MITs as viable alternatives to TURP for treating LUTS associated with BOO. While TURP remains highly effective, MITs, particularly aquablation and PAE, offer comparable functional outcomes with better safety profiles and preservation of sexual function.